A Preliminary, Open-Label Study of Naltrexone and Bupropion Combination Therapy for Treating Binge Drinking in Human Subjects. - Walter, T Jordan; Navarro, Montserrat; Thiele, Todd E; Pedersen, Cort; Kampov-Polevoy, Alexey; Garbutt, J C (Alcohol & Alcoholism, 2020)
Aims The combination of bupropion and naltrexone has shown efficacy in reducing binge drinking in animal models. This study assessed the tolerability and potential utility of combined naltrexone and bupropion in reducing binge drinking in human subjects. Methods This preliminary study employed an open-label, single-arm, 12-week, prospective design. Twelve men and women who exhibited a minimum of five (men) or three (women) binge drinking episodes per month over the past 3 months were recruited. All subjects received both bupropion-extended release 300 mg/day and naltrexone 50 mg/day and were monitored throughout the 3-month treatment period. Binge drinking was assessed using the timeline follow-back method. Results Treatment with combined naltrexone and bupropion reduced the average number of drinks per binge drinking day from 7.8 drinks to 6.4 drinks and reduced the average percentage of binge drinking days per month from 19% (5.7 days/month) to 5% (1.5 days/month). Naltrexone and bupropion were generally well tolerated, with insomnia, headache and nausea/diarrhea being the most common side effects. Six subjects elected to stay on medication after the trial. Conclusions This study suggests that combined naltrexone and bupropion therapy should be further investigated for tolerability and efficacy in reducing binge drinking in humans.